2016
DOI: 10.1038/srep38699
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 432 Pseudomonas strains through integration of genomic, functional, metabolic and expression data

Abstract: Pseudomonas is a highly versatile genus containing species that can be harmful to humans and plants while others are widely used for bioengineering and bioremediation. We analysed 432 sequenced Pseudomonas strains by integrating results from a large scale functional comparison using protein domains with data from six metabolic models, nearly a thousand transcriptome measurements and four large scale transposon mutagenesis experiments. Through heterogeneous data integration we linked gene essentiality, persiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 55 publications
5
57
0
Order By: Relevance
“…The core-genome of a taxonomic group contains genes that are present in all members of that group whereas the pan-genome contains all the different genes that can be found in any member of the population 30 . Here we extended the idea to protein domain classes, as has been previously reported 21,31 . We observed that most domain classes have a low persistence overall ( Figure 5), but as shown in Figure 6, by adding taxonomic information, distinct sets of domain classes accumulate in the core domainomes of the various clades, suggesting that these core sets are somehow contributing to the physiology and ecology of these clades.…”
Section: /15mentioning
confidence: 91%
“…The core-genome of a taxonomic group contains genes that are present in all members of that group whereas the pan-genome contains all the different genes that can be found in any member of the population 30 . Here we extended the idea to protein domain classes, as has been previously reported 21,31 . We observed that most domain classes have a low persistence overall ( Figure 5), but as shown in Figure 6, by adding taxonomic information, distinct sets of domain classes accumulate in the core domainomes of the various clades, suggesting that these core sets are somehow contributing to the physiology and ecology of these clades.…”
Section: /15mentioning
confidence: 91%
“…The DehI in the (10), and Pseudomonas putida AJ1 (23). To avoid potential misannotations, the selected genomes were de novo reannotated using the SAPP framework (46,47). Genes were identified using Prodigal (2.6.3) (48), and protein annotation was performed though protein domains using InterProScan (5.19-58.0) (49).…”
Section: Methodsmentioning
confidence: 99%
“…The genome was annotated using the SAPP annotation pipeline, (Koehorst et al, 2016a). For gene prediction Prodigal version 2.6.2 (Hyatt et al, 2010) with codon table 4 was used.…”
Section: Genome Annotationmentioning
confidence: 99%